(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
Background: Glycopeptides such as vancomycin are frequently the choice of antibiotics for the treatment of infections caused by methicillin resistant Staphylococcus aureus (MRSA). For the last 7 years incidence of vancomycin intermediate S. aureus and vancomycin resistant S. aureus (VISA and VRSA respectively) has been increasing in various parts of the world. Objective: The present study was carried out to find out the presence of VISA and VRSA among isolated MRSA strains. Methodology: This cross sectional study was carried out in the Department of Microbiology in Dhaka medical college during period of January 2010 to December 2011. All S. aureus isolates were screened to detect methicillin resistance and then all MRSA isolates were subjected for MIC testing against vancomycin and oxacillin by agar dilution method, disc diffusion testing and PCR for mecA and pvl genes detection. Result: A total 112 S. aureus were isolated from 500 nasal swab sample collected from adult patients who were admitted in various departments and wards in Dhaka Medical College Hospital. Among 38 MRSA strains out of 112 Staph aureus isolates 3(7.89%) strains were resistance to vancomycin of which 2(5.26%) strains had MIC > 256 mg/mL and one strain had MIC 256mg/mL. All vancomycin resistance strains had MIC of oxacillin > 256 mg/mL. All isolates possess mec-A gene. Conclusion: The present study reveals that emergence of VRSA upon admission at a tertiary care of hospital in Bangladesh. Continuous efforts should be made to prevent the spread and the emergence of VRSA by early detection of the resistant strains and using the proper infection control measures in the hospital setting. Bangladesh Journal of Infectious Diseases 2016;3(1):11-16